Designing for autism spectrum disorders - Gaines, Kristi; Bourne, Angela; Pearson, Michelle; Kleibrink, Mesha (New York : Routledge, 2016)
Winner of the IDEC 2017 Book Award Designing for Autism Spectrum Disorders explains the influence of the natural and man-made environment on individuals with autism spectrum disorders (ASD) and other forms of intellectual/developmental disabilities (IDD). Drawing on the latest research in the fields of environmental psychology and education, the authors show you how architecture and interior spaces can positively influence individuals with neurodiversities by modifying factors such as color, lighting, space organization, textures, acoustics, and ventilation. Now you can design homes, therapeutic environments, work environments, and outdoor spaces to encourage growth and learning for the projected 500,000 children with ASD (in the United States alone) who are expected to reach adulthood by 2024. Topics discussed include:-Environmental design theories-Symptoms of ASD-Sensory processing deficits -Design needs of individuals on the spectrum at all ages-Design methods and solutions for spaces, including residential, learning, work, and therapeutic environments encompassing a wide range of budgets-Designing for self-actualization, well-being, and a high quality of life for the duration of an individual's life-Avenues for healthy living and aging in place-Biophilic design-Environmental impact on well-being -Strategies to promote active living as an integral part of the welfare focus
Includes bibliographical references and index.
Keywords: Senses and sensation in architecture; Architecture -- Psychological aspects; Design -- Human factors